Zonation of the Eastern Ghats Mobile Belt: A Review - Sagar Misra; Aditya Kumar Mohanta; P Diwan; Neeraj Vishwakarma (Zenodo, 2015)
Eastern Ghats Mobile Belt (EGMB), a poly-cyclic, high grade metamorphic terrane occurs along the eastern margin of Indian subcontinent, bounded by the three Archean cratons along suture zone which relates to Indo-Antarctica collision. Along the boundary, alkaline rocks are present linearly and are believed to be formed during the crustal thickening process. Anorthosite plutons are emplaced in entire EGMB during different episodes and are thought to be formed during the rift formation associated with crustal thinning process. The main lithologies of EGMB are Charnockite-Enderbites, Metapelites, Leptynites, Mafic Granulites and Calc-silicate Gneisses. The characteristic metamorphic assemblages of the belt were developed during different stages of deformational history along with the imprints of Ultra High Temperature metamorphism. As far as the classification of the EGMB is concerned, different classification schemes have been proposed by different workers such as Zonal classification, Domain classification, Terrane classification and Province classification. Each classification has its own merits and demerits these have been summarized and discussed in this paper.